Adalékok a bánsági magyar nyelvű elemi oktatás történetéhez : 1718-2010 - Kókai, Sándor (Közép-Európai Közlemények, 2012)
After recapture of the Banat (1718) it has became one of the most various region of the Carpathian Basin in point of ethnics, languages and religions, where Hungarians were minority except some isolated group. The Hungarian education system could be established after the Austro-Hungarian Compromise of 1867, this was the last one in the case of great regions in the historical Hungary. As a result of the process there was not forced or impatient Hungarisation, but the nationalities could live like good neighbors, within interculturalism. After Treaty of Trianon a powerful fracture shocked the Hungarian primary education, nowadays it seems impossible to turn back the atrophy of Hungarian culture and language in Roman and Serb areas of the Banat. As a result the Hungarian villages and cultural islands disappeared from the 99% of Banat in practice. In our days every nationality, denomination or spiritual community is in disadvantageous situation, they loose even if the social and cultural ceremonies follow their plans. There are no winners in a war, which lasts for three centuries.